Reception. (17th September 2018) - Bridges, Emma; Paul, Joanna
Abstract : The cinematic and televisual reception of the ancient world remains one of the most active strands of classical reception study, so a new addition to the Wiley-Blackwell Companions series focusing on Ancient Greece and Rome on Screen is sure to be of use to students and scholars alike (especially given how often 'Classics and Film' courses are offered as a reception component of an undergraduate Classical Studies programme). The editor, Arthur Pomeroy, himself a respected and prolific 'early adopter' of this branch of scholarship, has assembled many of the leading names in cinematic reception studies (including Maria Wyke, Pantelis Michelakis, Alastair Blanshard, and Monica Cyrino), alongside a good number of more junior colleagues, resulting in a varied and rewarding compendium that will provide a useful accompaniment to more detailed explorations of this field. (Some, though not all, chapters offer further reading suggestions, and most are pitched at an accessible level.) The twenty-three contributions span the 'canonical' and already widely treated aspects of screen reception, from 1950s Hollywood epics to adaptations of Greek tragedy, as well as ranging across material which has only more recently began to attract the attention it deserves, such as TV documentary, or adaptations for younger audiences. The volume is not as easily navigable as it might be, with the four-part division of the chapters sometimes seeming a little arbitrary. (So, for example, a chapter which discusses 'The Return of the Genre' in films like Gladiator appears under the heading 'Comedy, Drama, and Adaptation', when it might have been better placed in the first section, on 'The Development of the Depiction of Ancient Greece and Rome on Screen'.) But rich discussions are not hard to find, especially in those chapters which show how cinematic receptions are indicators of more widely felt concerns relating to our reception of the past, as in Blanshard's assessment of 'High Art and Low Art Expectations: Ancient Greece in Film and Popular Culture'. Michelakis' chapter on the early days of cinema is also a valuable distillation of some of his recent work on silent film, crisply and concisely setting out the plurality of approaches that must inform our understanding of the cinematic medium (for example, spectatorship, colour, and relationships to other media). More broadly, the collection makes a solid and welcome attempt to put this pluralism into practice, with Pomeroy stressing 'the complexity of understanding film' early in his introduction (3). Chapters focusing on music, and costumes, for example, allow us to see productions 'in the round', a panoptical perspective which is still too readily avoided by much classical reception scholarship. (It is also good to see at least one chapter which ranges beyond screen media in the West.) Other vital areas of film and TV studies could arguably have received more attention. Some contributors touch on the importance of assessing audience receptions of these films, or the impact of marketing and other industrial considerations (such as screening practices), but more chapters dedicated to these approaches might have been a more sustained reminder to readers of just how widely screen scholarship can (and often needs to) range. To that end, a particularly significant chapter in the book – one of only 3 by non-Classicists – is Harriet Margolis' account of how film historians might evaluate ancient world film. Newcomers to this field should pay particular attention to this, and to Pomeroy's introductory comments on how we should regard film as much more than a quasi-literary medium.